Semi-continuous co-digestion of sludge, fallen leaves, and grass performance. (15th April 2021) - Elsayed, Mahmoud; Blel, Walid; Soliman, Mohamed; Andres, Yves; Hassan, Raouf
Abstract: The aim of this study is to improve the management of different types of wastes using an anaerobic digestion process and CH4 production from the semi-continuous co-digestion of multi-substrates of fallen leaves (FL), grass (GR) and primary sludge (PS). As a first step, the co-digestion of FL, GR and PS was carried out using the BMP test based on C/N ratios. The results showed that the best CH4 production was at a C/N ratio of 13. Kinetic analysis of the methane produced showed no adaptation phase was needed for the methanogenic bacteria to stimulate their anaerobic digestion activity. The inflection point in the cumulative methane production curve is identified as the biological hydrolysis phase of the substrates by endogenous microorganisms. In the second step, semi-continuous co-digestion of FL, GR and PS was carried out. The performance of the reactor was monitored in particular for biodegradability of the feedstock and biogas production rate under different OLRs. The highest biogas production rate of 35 L/d was recorded at an OLR of 1 g VS/L·d. However, partial overloading occurred at an OLR of 1.5 g VS/L·d. The highest CH4 content of biogas produced was achieved at an OLR of 1.0 g VS/L·d. Highlights: Semi-continuous co-digestion of multi-substrates of PS, FL, and GR was reported for an optimal methane production. The highest CMYs and VS removal rate were recorded at C/N ratios of 13 and 16, respectively. Kinetic analysis of the methane produced was conducted. The highest biogas production rate and methane content were recorded at an OLR of 1 g VS/L·d.